Implementation Processes of Social Protection Policy in Indonesia: Study of Prakerja Card Program - Fitri Kurnianingsih; Mahadiansar Mahadiansar; Ramadhani Setiawan (Journal of Governance and Public Policy, 2020)
In recent decades, in Indonesia, there have been many social protection policies as social and political agendas that are not public knowledge in the form of “Kartu Sakti”. One of the magic cards that are very popular during the COVID-19 pandemic is the Prakerja card. The purpose of this paper is to analyze the process of implementing the Grindle theory (2017) involving interest actors. The research method was carried out qualitatively by using secondary data which was analyzed in depth. The results show that the grindle theory includes Content of Policy and Content of Implementation in the social protection policy implementation process of the Prakerja card program, there are problems and are difficult to implement properly by the implementers, this causes the real purpose of social protection policies has not shown the impact on community welfare during the COVID -19 pandemic compared to other social protection policy programs on target. in addition, the actors of the Prakerja card program have different interests and goals from both the implementor and the recipient side. The Indonesian government is obliged to evaluate and take strategic and regulatory action in the form of pra Kerja program innovation as a long-term priority scale to avoid any gap in the process of implementing social protection policies that adversely affect the welfare of the Indonesian community.